Ethics in Postgraduate Research - Piña-Osorio, Juan Manuel (2017)
This article presents the results of an exploratory-descriptive research with empirical referents. The objective was to document, systematize and evaluate some features of 15 postgraduate theses in education, with the intention to make visible some recurring dishonest practices of students and teachers. The postgraduate programs from which the theses were obtained are located in the metropolitan area of Mexico City. The selection of documents was carried out between July and November 2015. Two Likert scales were used to assess two dimensions separately: 1) content, in which originality, congruence, dominance and relevance of authors, findings and relevant conclusions were considered; and 2) presentation, which examined style, logical structure, spelling and punctuation, citations, references and sources of information. Each indicator was assigned a numerical value and this one was given an evaluative characteristic: 5: excellent, 3: regular and 1: deficient. Subsequently, percentages were obtained. The results indicated that only a third of the theses could be classified as excellent for the quality of the content and the impeccable presentation; a similar percentage were works that fulfilled the necessary but didn’t count with the rigor and originality of the first ones. The remaining papers had serious deficiencies, both in content and in the formal presentation of the document, without achieving the minimum quality demanded by a postgraduate thesis. The analysis of these investigations made it possible to visualize some of the dishonest practices of people graduating from various educational programs and the lack of commitment to their research. The results about the quality of the research in various doctoral programs indicate that there is little responsibility in students, personal tutor and the reviewer. The results allow the authorities of each program to observe the problem and seek practical solutions to solve it.